2019
DOI: 10.3390/f10020171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Invasive Spartina alterniflora Loisel. and Subsequent Ecological Replacement by Sonneratia apetala Buch.-Ham. on Soil Organic Carbon Fractions and Stock

Abstract: Background and Objectives: The rapid spread of invasive Spartina alterniflora Loisel. in the mangrove ecosystems of China was reduced using Sonneratia apetala Buch.-Ham. as an ecological replacement. Here, we studied the effects of invasion and ecological replacement using S. apetala on soil organic carbon fractions and stock on Qi’ao Island. Materials and Methods: Seven sites, including unvegetated mudflat and S. alterniflora, rehabilitated mangroves with different ages (one, six, and 10 years) and mature nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 54 publications
4
10
0
Order By: Relevance
“…The influence of invasive species on the organic matter cycle has been reported previously, but this influence can be positive or negative [34]. Some authors state that this characteristic of invasive species can increase soil moisture and organic carbon [35,36], but our study revealed the opposite trend which was also correlated with studies by Feng et al [9]. Some ecosystems (forest systems especially) worldwide are able to storage carbon in soil that involves numerous components including biomass carbon and soil carbon [37] and every ecosystem stress (pollution, invasive status, etc.)…”
Section: Soil Physicochemical Propertiessupporting
confidence: 89%
See 1 more Smart Citation
“…The influence of invasive species on the organic matter cycle has been reported previously, but this influence can be positive or negative [34]. Some authors state that this characteristic of invasive species can increase soil moisture and organic carbon [35,36], but our study revealed the opposite trend which was also correlated with studies by Feng et al [9]. Some ecosystems (forest systems especially) worldwide are able to storage carbon in soil that involves numerous components including biomass carbon and soil carbon [37] and every ecosystem stress (pollution, invasive status, etc.)…”
Section: Soil Physicochemical Propertiessupporting
confidence: 89%
“…SOM is a property that influences soil function and directly influence soil health and quality of the environment [8]. Transformation of organic carbon in soils has a direct link to soil microbial attributes and some authors confirm that invasion has a positive effect on content of organic pool in soil ecosystems [9,10], the others showed the loss of organic matter in the specific valuable ecosystems [11,12]. Soil microbial community plays a key role in soil processes and soil enzymes catalyse reactions in soil system that have biochemical significance.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that any protection is better than none, and public ownership alone is as effective as some types of formal protection. In another study on plant invasions, Feng et al [7] examined the dynamics of invasion by smooth cordgrass (Spartina alterniflora Loisel.) and subsequent replacement by Sonneratia mangrove (Sonneratia apetala Buch.-Ham.)…”
Section: Contributions In Briefmentioning
confidence: 99%
“…Generally, pioneer mangrove species (e.g., Avicennia marina) often occur in seaward zones with low tidal gradients where the sediment pore water has relatively high salinity but low nutrients, while Rhizophoraceae mangroves are often located in the middle and/ or landward areas with lower flooding stress (Cheng et al, 2020). Furthermore, carbon stock and sequestration potential of sediments may vary significantly among different mangrove communities along a continuous tidal gradient during mangrove zonation (Feng et al, 2019;Chen et al, 2021a). Moreover, both EPS contents and producers (e.g., bacteria, fungi, and benthic diatoms) may also vary significantly with the variation in aboveground mangroves (Xiao and Zheng, 2016;Wang et al, 2019b;Mai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%